The Effect of Trust and Information Quality on Buying Decisions Through Purchase Interest: (Study Of Electronic Goods On Shopee Marketplace) - Yudanegara, Aditya (Indonesian Journal of Economics and Management, 2024)
This study aims to determine the influence of product quality, information quality on purchasing decisions through buying interest in online stores, case studies of electronic goods in the Shopee marketplace. This research is a quantitative research. The population in this study is all customers who have purchased electronic products through the Shopee online shop. The sampling technique uses purposive sampling with a total sample of 180 people. Data collection techniques use questionnaires that have been tested for validity and reliability. The data analysis technique used is linear partial (Partial Least Square / PLS). The results of this study show that: (1) there is a positive influence of product quality on purchasing decisions, (2) there is a positive influence of information quality on purchasing decisions, (3) there is a positive influence of product quality On buying interest, (4) there is a positive influence of product quality on buying interest, (5) there is an influence of product quality, quality of information on purchasing decisions through buying interest.